The effects of rubber swimsuits on swimmers measured by a lactic acid curve test - Shiraki, T.; Wakayoshi, K.; Hata, H.; Yamamoto, T.; Tomikawa, M. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: The rubber swimsuit was one of the causes of the record rush in 2009. Similar to wetsuit, the rubber swimsuit was made from Neoprene rubber. The effects of wearing a wetsuit on swimmers were widely reported. Tomikawa et al. suggested that the benefits of wearing a wet suit were not only the improvement in swimming propulsion efficiency, but the reduction in energy consumption. This study verified the influence of wearing the rubber swimsuit on the swimmer`s exercise load by using a lactic acid curve test. METHODS: Eight female university swimmers participated in this study. They performed the lactic acid curve tests with four different suits. They wore three types of rubber swimsuits and a cloth swim suit with water-repellent. All swimsuits were full-length type covering from shoulder to ankle. The lactic acid curve test consisted of 4 times 200m swimming. The speed of four stages in the test was set from the best record of each 200m freestyle race (80%V200, 85% V200, 90% V200, 95% V200). The speed was controlled by pace maker. Blood from the fingertip was taken 0 min and 3 min (5min) after each trial and the blood lactate was determined. RESULTS: The blood lactate concentration after 90% V200 and 95% V200 trials with rubber swimsuits tended to be lower than those with a cloth swimsuit (90% V200; rubber swimsuits 3.01±1.42 mmol/L, cloth swimsuit 3.89±1.37 mmol/L, 95% V200; rubber swimsuits 8.73±2.57 mmol/L, cloth swimsuit 10.46±2.57 mmol/L), but not significant. An examination of the trials revealed that the number of arm strokes decreased due to the use of the rubber swimsuits. DISCUSSION: It is suggested that the rubber swim suits improved propulsion efficiency and decreased swimmer exercise load same as wearing wetsuit, indicating that the rubber swimsuit may improve the race performance of swimmers.